From humans to AI: understanding why AI is perceived as the preferred co-creation partner - Liu, Yuchang; Yang, Yongzhong; Xu, Haoran (Frontiers in Psychology, 2025)
With the widespread adoption of generative AI in creative industries, individuals increasingly face a choice between human–human co-creation and human–AI co-creation. Prior comparisons of these modes have largely focused on output quality, efficiency, and user experience, while giving less attention to co-creation intention. Drawing on creativity theory, we argue that perceived novelty and perceived usefulness are the key mechanisms linking co-creator types to co-creation intention, and we test this account across four empirical studies. The results show that, relative to co-creating with humans, co-creating with AI significantly increases participants’ perceived novelty and, counterintuitively, perceived usefulness, thereby increasing co-creation intention. Qualitative interviews identify three principal drivers of why AI is regarded as more useful—efficiency, value, and relationship. Furthermore, we find that the need to belong exerts a moderating effect. Overall, this research extends creativity theory to the AI collaboration context, challenges the conventional assumption that “AI offers greater novelty whereas humans offer greater usefulness,” and uncovers social-motivational boundary conditions in technology-assisted creative work.